Defamation and Insult Through Information and Communication Technology Media According to Law No. 19 of 2016 Concerning Amendments to Law No. 11 of 2008 Concerning Electronic Transaction Information - Surian Surian; Maya Jannah; Abdul Hakim (Journal of Social Research, 2023)
This study examines Defamation and Insult through Information and Communication Technology Media According to Law No. 19 of 2016 Amendments to Law No. 11 of 2008 concerning Electronic Transaction Information which is the Indonesian Formil Law regarding the dissemination of information in the ITE Law, Criminal Code, Press Law, Human Rights Law, KIP Law and Constitutional Court Decision Number: 50 / PUU-VI / 2018, by using Normative Law research methods supported by the Concept approach (conceptual approach), Legislation approach (statue approach) and Case approach (case approach). The results of the author's research show that to be categorized as defamation, it must meet the elements contained in Articles 310 and 311 of the Criminal Code, namely "to be known to the public," meaning that defamation can be criminalized if what is intended is found by the public, according to the Constitutional Court Decision Number: 50 / PUUVI / 2008 which explains Article 27 paragraph (3) of the ITE Law is not a new norm because it must absolutely refer to the basic norms of Articles 310 and 311 of the Criminal Code, But on the contrary, if the element "to be known to the public" is carried out for public interest and self-defense, it cannot be subject to Article 27 paragraph (3) of the ITE Law jo Articles 310 and 311 of the Criminal Code, because journalists carrying out their profession as Journalists for the public interest is a statutory order as stipulated in the Basic Press Law Number 40 of 1999 including as a vehicle for social control that functions to cover, searching, collecting data and broadcasting and disseminating news so that the purpose is known to the public in line with the constitutional mandate contained in TAP MPR Number: XVII / MPR / 1998 concerning Human Rights.